Preliminary study of insects associated to indoor body decay in Colombia (2014)
ABSTRACT. Preliminary study of insects associated to indoor body decay in Colombia. This is the first report studying insects associated to indoor body decay process of a white pig (Sus scrofa) (Artiodactyla, Suidae) in a controlled indoor environment in an urban area of Florencia city, Amazonia Piedmont, Colombia. For a period of 54 days, 9,220 individuals (immature and adults), distributed in 3 orders, 5 families, 10 genera, and 10 species were collected using entomological nets and tweezers. Five decaying stages are described (fresh, bloated, active decay, advanced decay and remains). During the fresh stage we recorded Cochliomyia macellaria (Fabricius, 1775), Chrysomya albiceps (Wiedemann, 1819), Ophyra aenescens (Wiedemann, 1830), Oxysarcodexia sp., Lepidodexia sp. and Lasiophanes sp.; during the bloating stage C. macellaria, C. albiceps, Lucilia eximia (Wiedemann, 1819), Hemilucillia semidiaphana (Rondani, 1850), Musca domestica Linnaeus, 1758, O. aenescens, Oxysarcodexia sp., Lepidodexia sp., Dermestes maculatus De Geer, 1774 and Lasiphanes sp.; during the active decay C. macellaria, C. albiceps, L. eximia, M. domestica, O. aenescens, Lepidodexia sp. D. maculatus and Lasiophanes sp.; during the advanced decay C. macellaria, C. albiceps, M. domestica, Lepidodexia sp. and Lasiophanes sp.; and during the remains stage C. albiceps, D. maculatus and Lasiophanes sp. The insects were sorted out in 3 ecological categories; necrophagous, predators and parasites and sarco-saprophagous. According to Chao and Jack estimators, total richness was observed on day 20, with 100% of the expected species.